2018
DOI: 10.1016/j.bandl.2018.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Prosodic and phonetic subtypes of primary progressive apraxia of speech

Abstract: Primary progressive apraxia of speech (PPAOS) is a clinical syndrome in which apraxia of speech is the initial indication of neurodegenerative disease. Prior studies of PPAOS have identified hypometabolism, grey matter atrophy, and white matter tract degeneration in the frontal gyri, precentral cortex, and supplementary motor area (SMA). Recent clinical observations suggest two distinct subtypes of PPAOS may exist. Phonetic PPAOS is characterized predominantly by distorted sound substitutions. Prosodic PPAOS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 57 publications
4
89
0
6
Order By: Relevance
“…This has led to the recognition of subtypes of apraxia of speech: phonetic (formerly Type 1), prosodic (formerly Type 2), and mixed (formerly Type 3). 10,15 As mentioned previously, while several case reports and retrospective studies documented the occurrence of apraxia of speech as the initial manifestation of a degenerative disease, 7,8 prospective characterization of apraxia of speech as the sole manifestation of a neurodegenerative disease occurred within the past decade. Operational definitions for primary progressive apraxia of speech continue to be refined and, much like the criteria for PPA, require that features of other degenerative disorders are not present (TABLE 5-4).…”
Section: Primary Progressive Apraxia Of Speechmentioning
confidence: 88%
“…This has led to the recognition of subtypes of apraxia of speech: phonetic (formerly Type 1), prosodic (formerly Type 2), and mixed (formerly Type 3). 10,15 As mentioned previously, while several case reports and retrospective studies documented the occurrence of apraxia of speech as the initial manifestation of a degenerative disease, 7,8 prospective characterization of apraxia of speech as the sole manifestation of a neurodegenerative disease occurred within the past decade. Operational definitions for primary progressive apraxia of speech continue to be refined and, much like the criteria for PPA, require that features of other degenerative disorders are not present (TABLE 5-4).…”
Section: Primary Progressive Apraxia Of Speechmentioning
confidence: 88%
“…Note: ID, identification number; ASRS, Apraxia of Speech Rating Scale 3.0 (Utianski et al . ). The ASRS 3.0 yields a severity score between 0 (no features of AOS were observed in any task) and 52 (all AOS features nearly always evident and marked in severity).…”
Section: Methodsmentioning
confidence: 97%
“…The ASRS 3.0 yields a total score between 0 (no features of AOS were observed in any task) and 52 (all AOS features ‘nearly always evident and marked in severity’), which ‘captures the severity of the AOS but does not capture the specific quality of the AOS’ (Utianski et al . : 56). The spread of ASRS 3.0 scores for the participants covered a large range of AOS severity (8–31 out of 52 possible).…”
Section: Methodsmentioning
confidence: 97%
“…Several speech and language measures were administered as part of the standard research protocol, as previously reported (Duffy et al, 2017;Josephs et al, 2012Josephs et al, , 2013. Perceptual judgments of speech included (a) a 0-4 rating of AOS severity (1 = mild; 4 = severe), as an index of AOS severity regardless of its specific features; (b) a 1-10 rating (10 = normal) of MSD severity (adapted from Yorkston, Strand, Miller, & Hillel, 1993), which indexed the degree of functional impairment associated with the speech difficulty; (c) the Apraxia of Speech Rating Scale-Third Edition (ASRS-3), which quantified the severity and prominence of several AOS features, detailed below; and (d) an articulation error score (AES), also described below (Strand, Duffy, Clark, & Josephs, 2014;Utianski et al, 2018). Language measures included the Western Aphasia Battery (WAB; Kertesz, 2007), from which the Aphasia Quotients (AQs) served as a composite measure of global language ability; the WAB includes measures of repetition, naming, spontaneous speech fluency, word finding, grammatical competence, verbal and reading comprehension, and writing.…”
Section: Speech and Language Examinationsmentioning
confidence: 99%
“…Notably, research has demonstrated that the profile of initial AOS characteristics can differ among affected patients. In some cases, the speech pattern is dominated by distorted sound substitutions and additions and other features attributable to articulatory difficulty, whereas, in other cases, the pattern is dominated by slow, prosodically segmented speech (Utianski et al, 2018). The first profile has been designated as phonetic (articulatory) PPAOS and the second as prosodic PPAOS (previously referred to as Types 1 and 2, respectively; Josephs et al, 2013).…”
mentioning
confidence: 99%